TENSILE STRENGTH OF BONDING MATERIAL TO DENTINE USING WATER-WET AND ETHANOL-WET TECHNIQUES - Ainin Nafilatus; M. Mudjiono; Widya Saraswati (Conservative Dentistry Journal, 2018)
Background: Composite resins have hydrophobic properties so it cannot attach to dentine. Moist dentin is a normal condition caused by the presence of fluid in dentinal tubules. Therefore bonding material is required to bond dentine with composite. Water-wet technique is a technique in which dentine surface is rinsed after etching by using water and allowing it to be moist and prevent the collapse of dentine collagen fibrils. This technique is commonly used today, but excess water disturbs the effectiveness of dentine and bonding material attachment. Ethanol-wet technique is a technique in which ethanol is used to replace water before bonding to reduce excess water in dentine surface. This technique will initiate monomer penetration into interfibrillar space of dentine. It will affect the result of tensile strength test. Purpose: The purpose of this study was to compare tensile strength of bonding material to dentine using water-wet and ethanol-wet techniques. Method: 12 samples of bovine incisors teeth were randomly divided into 2 group. Each group consists of six samples. Group 1 was treated with water-wet technique and group 2 was treated with ethanol-wet technique. Autograph was used as a tensile strength test instrument. Result : The average of tensile strength using water-wet technique was 2,16067 MPa and ethanol-wet technique was 4,21900 MPa. Conclusion: Ethanol-wet technique have higher value of tensile strength than water-wet technique.